Galectin-3 Deficiency Facilitates TNF-α-Dependent Hepatocyte Death and Liver Inflammation in MCMV Infection - Stojanovic, Bojana; Milovanovic, Jelena; Arsenijevic, Aleksandar; Stojanovic, Bojan; Strazic Geljic, Ivana; Arsenijevic, Nebojsa; Jonjic, Stipan; Lukic, Miodrag L.; Milovanovic, Marija (Frontiers in Microbiology, 2019)
Galectin-3 (Gal-3) has a role in multiple inflammatory pathways. Various, opposite roles of Gal-3 in liver diseases have been described but there are no data about the role of Gal-3 in development of hepatitis induced with cytomegalovirus infection. In this study we aimed to clarify the role of Gal-3 in murine cytomegalovirus (MCMV)-induced hepatitis by using Gal-3–deficient (Gal-3 KO) mice. Here we provide the evidence that Gal-3 has the protective role in MCMV-induced hepatitis. Enhanced hepatitis manifested by more inflammatory and necrotic foci and serum level of ALT, enhanced apoptosis and necroptosis of hepatocytes and enhanced viral replication were detected in MCMV-infected Gal-3 deficient mice. NK cells does not contribute to more severe liver damage in MCMV-infected Gal-3 KO mice. Enhanced expression of TNF-α in the hepatocytes of Gal-3 KO mice after MCMV infection, abrogated hepatocyte death, and attenuated inflammation in the livers of Gal-3 KO mice after TNF-α blockade suggest that TNF-α plays the role in enhanced disease in Gal-3 deficient animals. Treatment with recombinant Gal-3 reduces inflammation and especially necrosis of hepatocytes in the livers of MCMV-infected Gal-3 KO mice. Our data highlight the protective role of Gal-3 in MCMV-induced hepatitis by attenuation of TNF-α-mediated death of hepatocytes.